2011
DOI: 10.1080/19768354.2011.604102
|View full text |Cite
|
Sign up to set email alerts
|

Steroidogenic acute regulatory protein (StAR) and peripheral-type benzodiazepine receptor (PBR) are decreased in human apoptotic embryos

Abstract: Fragmentation in human pre-implantation embryos has been suggested as the process of apoptosis. We have previously demonstrated a direct relationship between the increased reactive oxygen species (ROS) and apoptosis in human pre-implantation embryos. ROS is known to suppress the function of mitochondria in which steroidogenic acute regulatory protein (StAR) and peripheral-type benzodiazepine receptor (PBR) are presented. Therefore, the purpose of this study was to examine the expression of StAR and PBR in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…However, we observed that ONO-2952 effectively suppressed LPS-induced IL-1β mRNA expression in the hippocampus, whereas the germ-line knockout of TSPO did not suppress this cytokine in the present study. As TSPO is expressed as early as the preimplantation embryonic stage (27), a compensatory mechanism modifying the inflammatory response in the brain may occur during development. Although wild-type and knockout mice shared the same genetic background, i.e., C57BL/6J, and kept in the same environment at least 7 days before we started the experiment, we could not exclude the possibility that the growth environment contributed to the phenotypic difference between wild type and TSPOKO.…”
Section: Discussionmentioning
confidence: 99%
“…However, we observed that ONO-2952 effectively suppressed LPS-induced IL-1β mRNA expression in the hippocampus, whereas the germ-line knockout of TSPO did not suppress this cytokine in the present study. As TSPO is expressed as early as the preimplantation embryonic stage (27), a compensatory mechanism modifying the inflammatory response in the brain may occur during development. Although wild-type and knockout mice shared the same genetic background, i.e., C57BL/6J, and kept in the same environment at least 7 days before we started the experiment, we could not exclude the possibility that the growth environment contributed to the phenotypic difference between wild type and TSPOKO.…”
Section: Discussionmentioning
confidence: 99%